The potential of sweet orange (Citrus sinensis) in cardiovascular health: A literature review - Minami, Gabriella Stephanie; Lumbantoruan, Ellya Catharine; Puteri; Nuraini, Risa; Harianto, Joan Carmen; Fahrurroji, Andhi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Consumption of fast food and sedentary lifestyles has recently developed in society. This activity is one of the causes of various degenerative diseases, including cardiovascular disease. Therefore, efforts are needed to prevent it. Sweet orange (Citrus sinensis) is one of the most common types of citrus fruit, with total production reaching 70% of all types. This type of fruit is the most widely produced and consumed by the world’s population. Sweet orange is known for its bioactive compounds that have many benefits in cardiovascular health, such as alkaloids, flavonoids, tannins, phenols, vitamins C, B1, B2, and B3, glycosides, coumarin glycosides, folic acid, some organic acids, essential oils, and saponins. Flavonoids are components of secondary metabolites that play a role in the cardiovascular system. The main components of these compounds are hesperidin and naringenin. Various studies have shown that these compounds are active in reducing hyperlipidemia, improving endothelial function, acting as an anti-inflammatory and anti-atherosclerotic agent, preventing myocardial infarction, and preventing cardiac hypertrophy through various mechanisms with low toxicity.